SIFAT TERMAL DAN KELARUTAN DARI CYCLIC LIQUID NATURAL RUBBER - Leni Widiarti; Basuki Wirjosentono; Eddyanto Eddyanto (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2017)
Cyclic Liquid Natural Rubber (CLNR) is a cyclical natural rubber which has decreased molecular weight. Synthesis of Cyclic Liquid Natural Rubber (CLNR) can be done in a way that degradation after cyclization. Degradation after cyclization using Cyclic raw material Natural rubber (CNR), the degradation is done by using phenylhydrazine reagents with oxygen gas atmosphere with a flow rate of 2 LMenit-1 for 24 hours. CNR and CLNR thermal analysis by DSC, Tg results obtained amounted to 102.82 ° C and 103.67 ° C, Tc amounted to 362.45 ° C and 330.29 ° C and Tm mounted to 509.24 ° C and 440 , 00 oC. Of CNR and CLNR solubility test has a polarity index of 2.4 to 4.4 and from 2.4 to 4.4.